Simulation-based catastrophe-induced port loss estimation - Cao, Xinhu (2018)
Seaports are critical infrastructure systems in the international economy. They are at the same time vulnerable to various types of natural and man-made catastrophes due to their special coastal and low-lying locations. Traditional catastrophe risk analyses focused more on regions, port cities, and port communities. Limited studies assessed catastrophe risks on ports as a specific system. This paper aims to develop a catastrophe-induced port loss estimation framework, based on a port operation simulation model, actual terminal records and historical hazard records. By using the typhoon hazard and the Port of Shenzhen as a case study, we find that (1) the worst-case scenario of a typhoon impact could cause a total loss of US$0.91 billion for a terminal with 16 berths; and (2) the annual predicted typhoon-induced loss for the same terminal for the next 5 years will reach approximately US$64 million, accounting for 19.7% of the terminal net profit in 2015. The results provide useful references for various port stakeholders in catastrophe risk assessment and mitigation.